2013
DOI: 10.1016/j.brainres.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the calcium binding proteins Necab-1,-2 and -3 in the adult mouse hippocampus and dentate gyrus

Abstract: The family of EF-hand calcium binding proteins is composed of more than 250 members.In search for other neuronal markers, we studied the expression pattern of Necab-1, -2 and -3 in the Ammons horn of adult mice at the gene-and protein levels using in-situ hybridization and immunohistochemistry. The genes for the three Necab's were expressed in specific, non-overlapping areas of the hippocampus. A minority of the Necab-positive interneurons were GABA-ergic, and they virtually never coexpressed one of the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
5
10
0
Order By: Relevance
“…NECAB2 was highly expressed in the hippocampus and medial habenular nucleus, and moderately expressed in the cortex, thalamus, striatum, brainstem, and spinal cord (Fig. 11A-J), which is consistent with previous reports (Sugita et al, 2002;Zhang et al, 2016;Zimmermann et al, 2013). Double fluorescent labeling of GPR3 and NECAB2, using GPR3 knockout/LacZ knock-in mice, revealed that Ikawa et al Brain Research xxx (xxxx) xxx-xxx Fig.…”
Section: Co-expression Of Gpr3 With Necab2 In the Mouse Cnssupporting
confidence: 90%
See 1 more Smart Citation
“…NECAB2 was highly expressed in the hippocampus and medial habenular nucleus, and moderately expressed in the cortex, thalamus, striatum, brainstem, and spinal cord (Fig. 11A-J), which is consistent with previous reports (Sugita et al, 2002;Zhang et al, 2016;Zimmermann et al, 2013). Double fluorescent labeling of GPR3 and NECAB2, using GPR3 knockout/LacZ knock-in mice, revealed that Ikawa et al Brain Research xxx (xxxx) xxx-xxx Fig.…”
Section: Co-expression Of Gpr3 With Necab2 In the Mouse Cnssupporting
confidence: 90%
“…Aside from the classical EF-hand Ca 2+ -binding proteins, NECAB2 is the most attractive candidate to investigate the identity of cells that express GPR3; the distribution of NECAB2 is restricted to the CA2 region in the hippocampus (Gerber et al, 2019;Girard et al, 2015;Zimmermann et al, 2013), where GPR3 is predominantly expressed (Miyagi et al, 2016). Members of the NECAB family (NECAB1-NECAB3) contain a single EF-hand domain motif at the N-terminal and a DUF176 motif at the C-terminal, and both NECAB1 and NECAB2 are primarily expressed in the brain (Sugita et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Necab1 mRNA was also found in the temporal lobe of human brain (Wu et al, 2007). The recent in situ hybridization (and immunohistochemistry) study in mouse shows that Necab1 mRNA + neurons are scattered the hippocampus, whereas the Necab2 mRNA is strongly expressed in pyramidal neurons of CA2 (Zimmermann et al, 2013). Single-cell RNA sequencing has shown that both Necab1 and Necab2 transcripts are existed in mouse DRG neurons.…”
Section: Candidate Ef-hand Calcium-binding Proteinsmentioning
confidence: 94%
“…Very recently, NECAB1/2 were shown to have complementary expression patterns in mouse hippocampus at the mRNA and protein levels, whereas NECAB3 is broadly distributed in the hippocampus (29). NECAB1-expressing cells were seen throughout the cell-sparse layers of Ammon's horn and the hilus of the dentate gyrus.…”
Section: Significancementioning
confidence: 99%
“…In contrast, NECAB2 is enriched in pyramidal cells of the CA2 region. A minority of NECAB1 + neurons were GABAergic yet did not coexpress PV, CB, or CR (29).…”
Section: Significancementioning
confidence: 99%